An Analysis of Foreign Direct Investment, Human Capital Dynamics, and Policy Imperatives in Indonesia and ASEAN - Komalasari, Rita; Mustafa, Cecep (Sekretariat Jenderal DPR RI, 2024)
The primary purpose of this research is to provide a comprehensive understanding of the interplay between FDI and human capital in Indonesia. It seeks to fill gaps in the existing literature by adopting a regional perspective, conducting industry-level analysis, and evaluating multiple dimensions of human capital. Additionally, this study aims to offer tailored policy recommendations to assist Indonesia in escaping the middle-income trap and realizing its full economic potential. This research employs a literature approach. Our analysis reveals that FDI has distinct impacts on human capital dimensions, with variations across regions and industries. While Indonesia has attracted substantial inward FDI, disparities in wages and educational outcomes persist. The changing demand for skilled labor necessitates targeted policies for skills development. Territorial disparities in FDI attraction and human capital development also need to be addressed. The study culminates in a set of tailored policy imperatives aimed at guiding Indonesia towards sustained economic growth, reduced inequalities, and escaping the middle-income trap. These insights and recommendations are timely and essential as Indonesia charts its path in the evolving global economic landscape.